(untitled) (Journal of Parents and Teachers, 2025)
The article discusses the series Médico de familia; as its name suggests, it is a family series that presents various Spanish situations that reflect the realities that viewers experience daily. Throughout the series, family situations are developed, showing how all family members comment on and interfere in them.